2019
DOI: 10.5334/wwwj.40
|View full text |Cite
|
Sign up to set email alerts
|

The Struggle for Sustainable Waste Management in Hong Kong: 1950s–2010s

Abstract: As Hong Kong's landfills are expected to reach saturated conditions by 2020, the city can no longer rely on landfilling alone as the sole solution for waste treatment in the long term. Drawing on five months of archival research at the University of Hong Kong and the Hong Kong Public Records Office (PRO) in 2016 as well as 17 months of fieldwork conducted between 2012, 2013 and 2016, this article provides a muchneeded overview of why sustainable waste management has always been such a challenge for Hong Kong. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Waste becomes a useful tool in a variety of political conflicts, because waste can become a physical representation of the political claims of a group (Chalfin, 2014; Fredericks, 2018). Waste management can then be an important site of claim‐making, creating novel ways for interest groups to interact with elected or state officials (Wu & Martus, 2021; Fabian & Lou, 2019; Ahmann, 2019).…”
Section: Waste and Its Management: How Waste Becomes Politicizedmentioning
confidence: 99%
“…Waste becomes a useful tool in a variety of political conflicts, because waste can become a physical representation of the political claims of a group (Chalfin, 2014; Fredericks, 2018). Waste management can then be an important site of claim‐making, creating novel ways for interest groups to interact with elected or state officials (Wu & Martus, 2021; Fabian & Lou, 2019; Ahmann, 2019).…”
Section: Waste and Its Management: How Waste Becomes Politicizedmentioning
confidence: 99%
“…In practice, studies from Fok (2016: 16) and Xiao and Siu (2018: 178) identified convenience consideration, availability of physical infrastructure, technical facilities, and public facilities, as well as on-site implementation and management as contextual factors which are highly correlated with sustainable and pro-environmental behavioural change in MSWM. In respect of the physical infrastructure, technical facilities and availability of public facilities, some scholars have addressed some connected factors, including: the perceived needs for the facilities concerned; the perceived impacts and risks; the perceived fairness of the process; and the public’s trust in those who make decisions (Fabian and Lou, 2019; Lam and Woo, 2009). Regarding the implementation and management, it is essential to look through the process of carrying out, accomplishing, fulfilling, producing, and completing a policy (Pressman and Wildavsky 1973: xiii).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although panaceas for the MSWM and governance problems are plentiful, history suggests that Hong Kong’s MSWM and governance issues are unlikely to be resolved unless the government learns from its past failures and is willing to adopt a more proactive approach (Fabian and Lou, 2019: 1). It is imperative that the Hong Kong government proactively learns from the past failures, especially in the purview of source separation of MSW collection.…”
Section: Options and Prospects – Learning From Other Countries Partnmentioning
confidence: 99%
See 2 more Smart Citations